Why older workers work beyond the retirement age: a qualitative study - Sewdas, Ranu (BMC Public Health, 2017)
BACKGROUND: The aims of the present study were to: 1) gain insight into reasons for working beyond the statutory retirement age from older workers’ perspectives, and 2) explore how the domains of the research framework Study on Transitions in Employment, Ability and Motivation (STREAM) can be applied to working beyond retirement age. METHODS: A qualitative research design included individual interviews (n = 15) and three focus groups (n = 18 participants) conducted with older workers aged 65 years and older continuing in a paid job or self-employment. Interview participants were recruited from an existing STREAM cohort study. Focus group participants were recruited from companies and employment agencies. The data were subjected to thematic analysis. RESULTS: The most important motives for working beyond retirement age were maintaining daily routines and financial benefit. Good health and flexible work arrangements were mentioned as important preconditions. The themes emerging from the categorization of the motives and preconditions corresponded to the domains of health, work characteristics, skills and knowledge, and social and financial factors from the STREAM research framework. However, our analysis revealed one additional theme—purpose in life. CONCLUSION: This study offers important new insights into the various preconditions and motives that influence working beyond retirement age. In addition, the five domains of the STREAM research framework, including the additional domain of ‘purpose in life’, seem to be applicable to working beyond retirement age. This knowledge contributes to the development of work-related interventions that enhance older workers’ motivation to prolong their working lives.